An analysis of barriers to waste recycling in Seremban using descriptive analysis, Interpretive Structural Modelling (ISM) and Decision-Making Trial and Evaluation Laboratory (DEMATEL) / Ashiera Nadiha Hazri, Nurul Ain Syahirah Mohd Azri and Nurul Dania Farisha Sharul Rhmdan - Hazri, Ashiera Nadiha; Mohd Azri, Nurul Ain Syahirah; Sharul Rhmdan, Nurul Dania Farisha (2023)
Waste recycling is described as any recovery technique used to transform waste into new goods, resources, or substances that can be used for the original or other uses. The Malaysian government through the Ministry of Housing and Local Government has spent millions of Ringgits over the past few years in advertisements and campaigns related to recycling. However, there has been little previous research that has used the DEMATEL or ISM methods, but both of the methods will be used to conduct this research. While DEMATEL focuses on finding important system components and differentiating between cause and effect factors. There were no study using DEMATEL to find the barriers to waste management in Malaysia. This study aims to determine the barriers of the households recycling in Seremban by using descriptive analysis, to apply the Decision-Making Trial and Evaluation Laboratory (DEMATEL) cause and effect in barriers to waste recycling and the third one is to identify relationships among barriers to waste recycling using Interpretive Structural Modelling (ISM). From the descriptive analysis, it shows that physical barriers is the highest barriers of waste recycling among households in Seremban. For DEMATEL method, it demonstrate a cause-and-effect relationship, demonstrating that lack of recycling facilities has the greatest influence on other barriers. By using ISM method, the highest barriers of waste recycling among households in Seremban are lack of motivation / information on recycling options, convenience-related barriers and social norms.